KARAKTERISTIK SIFAT ZUHUD MENURUT HADIS NABI SAW - Abd. Wahid Abd. Wahid (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
A person who is called a zuhud is at least characterized by three kinds of traits: not overly excited by what he has gained from earthly things, not too saddened by what is lost from him; and not preoccupied with the search and enjoyment of the world so that it neglects something more important in the sight of God. Some people think that zuhud is just a matter of leaving the treasure, because leaving the treasure and showing poverty is an easy thing to do by anyone who wants to say people that he is a zahid. Actually zuhud is the attitude of sincerity in the heart against the limitations and advantages possessed. Zuhud also has a meaning against the passions of the temptations of material nature. Lust is the covering of all worldly desires, then zuhud is to abolish that attitude. Zuhud also does not live in poverty and simple circumstances caused by the inability of a person to gain luxury and wealth, but zuhud is to leave the luxury solely for the sake of achieving Allah's pleasure. In other words, it is not said zuhud for the poor because they can not afford to seek a better life.